The end [compact disc, unabridged] - Snicket, Lemony (Snicket, Lemony. Series of unfortunate events, 2006)
Lost at sea, the Baudelaire orphans, along with the evil Count Olaf, wash up on the shore of an island populated by an oddly placid group of inhabitants, and they try to decide whether or not they are truly safe.